2017
DOI: 10.1364/boe.8.004396
|View full text |Cite
|
Sign up to set email alerts
|

Generation and optimization of superpixels as image processing kernels for Jones matrix optical coherence tomography

Abstract: Jones matrix-based polarization sensitive optical coherence tomography (JM-OCT) simultaneously measures optical intensity, birefringence, degree of polarization uniformity, and OCT angiography. The statistics of the optical features in a local region, such as the local mean of the OCT intensity, are frequently used for image processing and the quantitative analysis of JM-OCT. Conventionally, local statistics have been computed with fixed-size rectangular kernels. However, this results in a trade-off between im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…The DOPU algorithm, therefore, averages the Stokes components over adjacent speckles, and the underlying polarization scrambling results in a decreased DOP in the evaluation window. Based on DOPU, several improvements concerning its noise sensitivity, orientation dependency, and evaluation kernel size have been proposed 9,[17][18][19][20] and enhance depolarization imaging as a powerful tool for several biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The DOPU algorithm, therefore, averages the Stokes components over adjacent speckles, and the underlying polarization scrambling results in a decreased DOP in the evaluation window. Based on DOPU, several improvements concerning its noise sensitivity, orientation dependency, and evaluation kernel size have been proposed 9,[17][18][19][20] and enhance depolarization imaging as a powerful tool for several biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Miyazawa et al demonstrated pixel grouping for JM-OCT, superpixelization [143]. In this method, the pixels in a crosssectional JM-OCT image are mapped into a six-dimensional feature space of four JM-OCT contrasts and two (lateral and axial) spatial dimensions.…”
Section: B Jm-oct Specific Image Processingmentioning
confidence: 99%
“…[54] combined superpixel with LogitBoost adaptive boosting to detect glaucomatous damage in 3D OCT images. In [44], the superpixel technique was applied to generate the flexible kernels of local statistics on the Jones matrix-based polarization sensitive OCT.…”
Section: Related Workmentioning
confidence: 99%